Application of commercial sand aggregates in hydrophobized hydraulic concrete materials - Mora, Ernesto (2024)
Because precursors such as sand are generally accessible, concrete has become a widely used construction material. Not all available sands, however, fulfill the requirements of purity, granulometry, shape and porosity for use in concrete materials. Here we report the setting of the hydrophobicity of hydraulic concrete matrices prepared with commercial sands and hydrophobic silica particles (dodecyl-modified silica) added to their mixtures.  The granulometry and porosity of the selected fine aggregates were confirmed to influence the water absorption of hydrophobized concrete matrices. Water absorption decreased more than 30 % on addition of silica hydrophobized with dodecyl. As the functionalization was performed from the mix prepared with commercial sands, an improved hydrophobicity of the materials was provided integrally to the matrix.